2023
DOI: 10.3390/foods12071459
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Power of Thermosonication: A Comprehensive Review of Its Applications and Impact in the Food Industry

Abstract: Thermosonication (TS) has been identified as a smart remedy for the shortcomings of heat treatment, which typically requires prolonged exposure to high temperatures. This technique combines moderate heat treatment with acoustic energy to eliminate harmful microorganisms and enzymes in food products. Unlike conventional heat treatment, thermosonication utilizes short holding times, allowing for the preservation of food products’ phytochemical compounds and sensory characteristics. The benefits and challenges of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 139 publications
1
5
0
Order By: Relevance
“…An increase in TCC under TS treatment may be observed due to the prior cavitation effects on enzyme inactivation and generation of several bioactive compounds. 40 A similar observation was reported for TS juice from cashew apple, spinach and star fruit. 13,28,41 A lower thermosonication amplitude indicates that the mechanical effects (acoustic cavitation) generated within the liquid are less intense.…”
Section: Total Carotenoid Content (Tcc)supporting
confidence: 76%
“…An increase in TCC under TS treatment may be observed due to the prior cavitation effects on enzyme inactivation and generation of several bioactive compounds. 40 A similar observation was reported for TS juice from cashew apple, spinach and star fruit. 13,28,41 A lower thermosonication amplitude indicates that the mechanical effects (acoustic cavitation) generated within the liquid are less intense.…”
Section: Total Carotenoid Content (Tcc)supporting
confidence: 76%
“…The thermosonication method is a new food processing technique created by applying ultrasound with temperature control. It has been reported that thermosonication, which has recently gained popularity in food processing, provides microbial decontamination and protection while being reliable and environmentally friendly [10][11][12][13][14]. During the thermosonication process, it is essential to consider variables such as the temperature, pH, amplitude and processing time of the product to ensure the effectiveness of the process.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasonic transducer is responsible for the conversion of energy, transforming the signals or energy from another source into the necessary ultrasonic signals or energy. There are numerous types of ultrasonic transducers available, each designed to fulfill specific requirements and perform particular functions [168] , [169] . In terms of electroacoustic ultrasonic transducers, there are piezoelectric transducer, magnetostrictive transducer, electric transducer and electromagnetic transducer, etc.…”
Section: Ultrasonic Assisted Extraction Equipment (Uaee)mentioning
confidence: 99%